2020
DOI: 10.1109/access.2020.3029446
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Drug Risk Level from Adverse Drug Reactions Using SMOTE and Machine Learning Approaches

Abstract: Adverse drug reactions (ADRs) are the major source of morbidity and mortality. The prediction of drug risk level based on ADRs is few. Our study aims at predicting the drug risk level from ADRs using machine learning approaches. A total of 985,960 ADR reports from 2011 to 2018 were attained from the Chinese spontaneous reporting database (CSRD) in Jiangsu Province. Among them, there were 887 Prescription (Rx) Drugs (84.72%), 113 Over-the-Counter-A (OTC-A) Drugs (10.79%) and 47 OTC-B Drugs (4.49%). An over-samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…For each dataset (Tumor Grade Dataset n � 245 and Overall Survival Dataset n � 150), data were randomly split into training and testing sets with a test size � 0.2, yielding training sets containing 196/120 samples and testing sets containing 49/30 samples, respectively. To prevent the class imbalances from affecting the models' performance, we applied the synthetic minority oversampling (SMOTE) [26] technique to the tumor grade training dataset due to the existing radiomics studies that have shown SMOTE can effectively improve the classification predictive performance when the classes are imbalanced. However, SMOTE was not applied to the Overall Survival Dataset since classes were already balanced.…”
Section: Methodsmentioning
confidence: 99%
“…For each dataset (Tumor Grade Dataset n � 245 and Overall Survival Dataset n � 150), data were randomly split into training and testing sets with a test size � 0.2, yielding training sets containing 196/120 samples and testing sets containing 49/30 samples, respectively. To prevent the class imbalances from affecting the models' performance, we applied the synthetic minority oversampling (SMOTE) [26] technique to the tumor grade training dataset due to the existing radiomics studies that have shown SMOTE can effectively improve the classification predictive performance when the classes are imbalanced. However, SMOTE was not applied to the Overall Survival Dataset since classes were already balanced.…”
Section: Methodsmentioning
confidence: 99%
“…To address the bias problem in the training set, the synthetic minority oversampling technique (SMOTE) [ 38 ], a data augmentation approach that has been widely used in previous research, was applied in this study [ 39 , 40 , 41 , 42 ]. The SMOTE was accomplished by the imbalanced-learn package [ 43 ] (vision 0.8.0).…”
Section: Methodsmentioning
confidence: 99%
“…e confusion matrix table is useful to quantify the number of misclassifications for both the negative and positive classes [55]. e total sample size used during testing is the sum of TN, FN, TP, and FP as per the blueprint of the confusion matrix.…”
Section: E Confusion Matrix " E Confusion Matrix Tablementioning
confidence: 99%
“…e prediction score was used to calculate the average precision (AP). At each threshold, the weighted mean of precisions achieved, with the increase in recall from the preceding threshold used as the weight, is how AP summarizes a precision-recall curve [55]:…”
Section: E Precision-recall Curvementioning
confidence: 99%